Monopolistic Competition, Layoffs and Perishable Sectors - Cabral, Célia Costa (1996)
This paper develops a general equilibrium model with monopolistic competition à la Dixit and Stiglits. In this economy, demand changes over time, generating the need for firms to vary the number of workers hired each time period. We show that, in such an economy, if restrictions are introduced on the ability of firms to layoff workers, employment rises in the short-run, but it may either rise or fall in the long-run. This depends on two opposite-sign effects on the optimal choice of leisure. One, vastly discussed in the literature, is that goods will in general be older, which will increase the demand for leisure. The other, which has been somewhat overlooked in the literature, is that each firm's life will be longer, which will increase the demand for labor and decrease the demand for leisure. Welfare may increase, if employment has also increased, since leisure consumption was initially higher than socially optimal.